Logistic regression using the SAS system theory and application - Allison Paul D (New jersey John Wiley, 2003)
Topics are covered: binary logit analysis, logit analysis of contingency tables, multinomial logit analysis, ordered logit analysis, discrete-choice analysis with the PHREG procedure, and Poisson regression. Other highlights include discussions of how to
Keywords: Logistic models; Regression analysis